Bioaccumulation of Pb and Cd on Broiler Chicken Fed in Difference Diets - Bambang Dwiloka; U. Atmomarsono; V. Priyo Bintoro; B. Widianarko (International Journal of Science and Engineering, 2012)
The study was aimed to compute Pb and Cd bioaccumulation in different organs of broiler. Carcass, heart, liver, gizzard, intestine, and excreta. The data were obtained from broiler reared in the litter cage. Four treatments of feed were given to the broiler chicken, i.e.  T1 = X brand of commercial feed, T2 = Y brand of commercial feed, T3 = self-prepared feed without fish meal addition and T4 = self prepared feed without fish meal but contaminated with cadmium chloride (Cd.Cl2.4H2O). For each treatment, five broiler chicken were grouped each week (from week I up to week VI). Results of the first stage of this study was analyzed descriptively. A polinomial regression equation was used as an empirical model to describe the heavy metal bioaccumulation phenomenon in broiler carcasses. The quadratic equation  turned out to be the most suitable model for describing the bioaccumulation of heavy metal in broiler carcasses. From the simulation, it was found that  quadratic model fit to 61.31% and 54.17%  bioaccumulation data of Pb and Cd respectively. According to the model, initially metal concentrations declined since the first week and started to rebound at the fifth week, both in terms of chronological and physiological age. The patterns of Pb and Cd bioaccumulation in this study can be used as a reference to determine the proper slaughter period. It can be concluded that for reducing the risk of metal contamination the proper slaughter time of the broiler is before the fifth week.